The efficacy of intense pulsed light and heat energy therapy compared to benzoyl peroxide gel 2.5% in the treatment of mild and moderate acne vulgaris - Triasari Oktavriana; Agnes Sri Siswati; Kristiana Etnawati (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 2015)
The use of technology-based light therapies such as intense pulsed light and heat energy(IPL) provides an alternative therapy for patients with acne. However, clinical evidenceis required to evaluate the efficacy and safety of the IPL. This study aimed to evaluate theefficacy of IPL compared to benzoyl peroxide (BP) as standard therapies in patients withacne vulgaris. The study was conducted with randomized controlled trial parallel designinvolving patients with mild and moderate acne vulgaris. Acne severity was determined bythe method of Combined Acne Severity Classification (CASC). Statistical analysis usingrepeated measurement analysis of variance was conducted to assess the reduction inlesions and number of P. acnes in each group followed by independent t-test to compareof both groups. A p value <0.05 was considered significant. Sixty-two patients withmild and moderate acne vulgaris were enrolled in this study and treated with IPL (32patients) and with BP gel 2.5% (30 patients). Two patients from the IPL were droppedout. All subjects showed improvement in acne lesions. Reduction of the number ofnon-inflammatory lesions at IPL therapy group was not significantly different than theBP gel 2.5% at week 2 (p=0.705) and 4 (p=0.186). Reduction in the numberof inflammatory lesions in the IPL treatment group was not significantly different than BPgel 2.5% at week 2 (p=0.604) but significantly higher at week 4 (p=0.003). Thereduction of P. acnes colonization in the IPL group was significantly higher than BP gel2.5% group at week 2 (p=0.000) and 4 (p=0.000). In conclusion, the efficacy of IPLin the reduction of the number of inflammatory lesions and the P. acnes colonization isbetter than BP on patients with acne vulgaris.